Hubungan antara Tingkat Pengetahuan Pasien dan Pengawas Menelan Obat (PMO) dengan Kepatuhan Pasien Tuberkulosis di Puskesmas Kabupaten Jember - Antonius Nugraha Widhi Pratama; Amelya Prastica Rahayu Aliong; Nili Sufianti; Ema Rachmawati (Pustaka Kesehatan, 2018)
Tuberculosis (TB) is an infectious disease that mostly affects developing countries. In Indonesia, TB incidence increases every year due to patient inadherence to the standard DOTS therapy. The TB patients inadherence can be associated with poor knowledge among patients and treatment observers. This cross-sectional research aimed to explore the correlation between knowledge level of TB patients and their treatment observers and patient adherence. Purposive sampling technique was used to collect data from 65 respondents from their primary health centers in Jember Regency, East Java. Knowledge of the respondents was evaluated using a 16 items questionnaire and patient adherence was assesed using the translated version of morisky medication adherence scale-8 (MMAS-8) questionnaire. The Spearman Rho correlation test resulted in p value of 0,043 between patients knowledge and patients adherence. Statistically significant correlation was also found between the knowledge of treatment observers and TB patients adherence (p= 0,015). These results suggested the needs to improve knowledge about TB not only for TB patients, but also their treatment observers. Keywords: TB patient, treatment observer, knowledge, compliance